Teacher’s perception on student’s self-regulated learning in a technology-based learning setting - Deafey Majitol; Melor Md Yunus (Institute of Advanced Engineering and Science, 2023)
It was inevitable that during the COVID-19 pandemic, various teaching and learning experiences were taken into virtual platforms. With the direct and total integration of technology in education during the pandemic, students had to rely mostly on their own self-regulated learning in order to progress in their learning. This systematic review explored teachers’ perception on students’ self-regulated learning (SRL) in a technology-based learning (TBL) setting. By using the preferred reporting items for systematic review and meta-analyses (PRISMA) 2020 as the review methodology, 39 articles were selected from the databases of ERIC and Google Scholars to complete this study. Findings revealed that teachers perceive the following factors to play a significant part for SLR and TBL to complement each other: i) Digital educational resources and accessibility for both teachers and students; ii) Teacher and student’s readiness and competencies regarding technology-based learning; and iii) Parents’ involvement in students’ self-regulated learning for security and motivational purposes. It is believed that by implementing student-centered approach with the facilitation of various education stakeholders, students’ learning can occur more effectively, purposeful and meaningful. Future research suggests an investigation on students’ self-regulated learning from the perspective of parents and other related social issues.